Promotion of knowledge, attitude, and practice among medical undergraduates regarding infection control measures during COVID-19 pandemic - Saati, Abdullah A.; Alkalash, Safa H. (Frontiers in Public Health, 2022)
Background: Medical students expose for many serious health care-associated infections throughout their learning and training time particularly during pandemic like COVID-19. Therefore, promotion of their knowledge, attitude and practice regarding infection control measures is a mandatory action. Objective: This study was executed to evaluate the knowledge, attitude, and practice of medical undergraduates towards infection control measures before and after implementation of practical infection control training for them. Methods: A quasi-experimental prospective study was conducted on a simple random sample of medical undergraduates in Al-Qunfudah College of medicine, Umm Al-Qura University, KSA. A total of 177 medical undergraduates were recruited in this study and completed a predesigned survey on their knowledge regarding infection control measures. Moreover, their practicing to infection control measures was evaluated through a checklist before and six months after receiving a practical infection control training during their academic year 2020-2021. Results: A total of 177 and 176 responses were obtained at pre-test and post-test respectively. Mean ages of students who participated in pre-training and post training assessments were (22.50±1.02 &22.03±1.34) respectively with female sex predominance (62.1&61.9%). Mean knowledge and practice scores among them were enhanced from (7.79±2.10 and 4.56±2.58) at their pre-test to (11.06 ± 1.27 and15.68±1.90) at post-test (P value 0.001 and <0.001) respectively. After training almost all of them recommended infection control training for all medical students due to its great value. Conclusion: The training course has shown its capability in promotion of medical undergraduates' knowledge, attitude and practice towards infection control measures.